The Influence of Educational Games in Problem-Based Learning on Student Learning Outcomes in Informatics Subjects at SMP Negeri 1 Angkola Barat - Siregar, Alfi Salimah; Efrizon, Efrizon; Dewi, Ika Parma; Jasril, Ilmiyati Rahmy (Jurnal Pengabdian Nusantara, 2025)
This research aims to determine the effect of using Wordwall-based educational games in Problem-Based Learning (PBL) on the learning outcomes of Informatics subject at SMP Negeri 1 Angkola Barat. The research method used is a quasi-experimental design with a non-equivalent control group design approach. The research sample consists of two classes: the experimental class using Wordwall educational games in PBL-based learning and the control class using conventional methods. Data collection was carried out through pretest and posttest to measure students' learning outcomes. The analysis results show that the data are normally distributed and homogeneous, so an independent t-test was conducted. The calculated t-value of 3.04 is greater than the t-table value of 2.002 with a significance of 0.004 (<0.05), indicating a significant difference between the two groups. The posttest mean score for the experimental class was 87.83, while for the control class it was 80.63, demonstrating a significant improvement in students' learning outcomes through the use of educational games. The results of this research affirm that integrating interactive learning media such as Wordwall in PBL can enhance students' motivation, engagement, and understanding of Informatics material, serving as an effective alternative in 21st-century learning.